2019
DOI: 10.26503/todigra.v4i3.104
|View full text |Cite
|
Sign up to set email alerts
|

Are Loot Boxes Gambling? Random Reward Mechanisms in Video Games

Abstract: In this paper we investigate the phenomenon colloquially known as “loot boxes”. Loot boxes became a hot topic towards the end of 2017 when several legislative bodies proposed that they were essentially gambling mechanisms and should therefore be legislated as such. We argue that the term “loot box” and the phenomena it covers are not sufficiently precise for academic use, and instead introduce the notion of “random reward mechanisms” (RRMs). We offer a categorization of RRMs, which distinguishes between RRMs t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
81
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(82 citation statements)
references
References 11 publications
0
81
0
1
Order By: Relevance
“…King and Delfabbro viewed loot boxes as only one type of 'predatory monetization'. This perspective is comparable to that of Nielsen and Grabarczyk (2018), who, from historical and ludological perspectives, suggested that loot boxes are only 'a particular implementation of a more general phenomenon', which they coined Random Reward Mechanisms (RRMs) (pp. 2-3).…”
Section: The Expanding Definition Of 'Predatory Monetisation' and 'Rrms'mentioning
confidence: 64%
See 1 more Smart Citation
“…King and Delfabbro viewed loot boxes as only one type of 'predatory monetization'. This perspective is comparable to that of Nielsen and Grabarczyk (2018), who, from historical and ludological perspectives, suggested that loot boxes are only 'a particular implementation of a more general phenomenon', which they coined Random Reward Mechanisms (RRMs) (pp. 2-3).…”
Section: The Expanding Definition Of 'Predatory Monetisation' and 'Rrms'mentioning
confidence: 64%
“…6-7). Nielsen and Grabarczyk (2018) argued that the classic mechanic of killing an in-game enemy for a random in-game reward of no real-world value constitutes a historical implementation of an RRM (pp. 3-4).…”
Section: Predatory Addiction-inducing Time-consumption?mentioning
confidence: 99%
“…Taking into account the historical development of video games, Nielsen and Grabarczyk (2019) argued that loot boxes are only 'a particular implementation of a more general phenomenon,' which they coined 'Random Reward Mechanisms' (RRMs), which have been implemented in video games for decades (pp. 173-175 The 'eligibility condition' refers to how the player is able to 'trigger the random procedure.'…”
Section: Categorising Loot Boxes As Rrmsmentioning
confidence: 99%
“…'Loot boxes' are virtual video game items yielding randomised rewards of in-game and potential real-world value (Drummond et al, 2020;Nielsen and Grabarczyk, 2019;Rockloff et al, 2020;Xiao, 2020c). Some loot boxes can be 'opened' for free, e.g., after completing in-game tasks (Nielsen and Grabarczyk, 2019;Rockloff et al, 2020;Xiao, 2020d). However, this paper focuses on paid loot boxes that require payment of real-world money to open.…”
Section: Loot Boxes Disordered Gambling and Regulationmentioning
confidence: 99%